PEMBELAJARAN IPS DI SEKOLAH DASAR - Parni Parni (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2020)
Learning and teaching are two concepts that are interrelated in the teaching and learning process and their effectiveness can be achieved by utilizing learning resources. Related to social studies learners, which social studies learning is a lesson that learns about social life and where the application of social studies learning at the primary school education level is not only oriented to social development, but also oriented to the development of critical thinking skills, and students' basic skills. which side with the realities of social life. Humans as social beings always live together and need one another, therefore as social beings in carrying out a job can be carried out by working together. And create a sense of tolerance in order to create harmony and peace in social life.